Fulminant Necrotizing Enterocolitis and Multiple Organ Dysfunction in a Toddler with Mitochondrial DNA Depletion Syndrome-13 - Nardi, Nicolas; Proulx, François; Brunel-Guiton, Catherine; Oligny, Luc L.; Piché, Nelson; Mitchell, Grant A.; Joyal, Jean Sébastien (Journal of Pediatric Intensive Care, 2020)
Necrotizing enterocolitis (NEC) is exceptional after the neonatal period. A toddler with encephalopathy, mitochondrial myopathy, and hypertrophic cardiomyopathy developed fatal NEC and multiple organ dysfunction within 48 hours of the introduction of enteral feeding. She was subsequently found to have pathogenic mutations in FBXL4, a cause of mitochondrial DNA depletion syndrome-13. Intestinal dysmotility in the context of deficient mitochondrial respiration may have contributed to the development of NEC. Current paradigms call for early introduction of enteral nutrition to reinstate energy homeostasis. Enteral feeding should be administered with caution during metabolic crises of patients with mitochondrial DNA depletion syndromes.
Keywords: necrotizing enterocolitis; mitochondrial DNA depletion syndrome; FBXL4; multiple organ dysfunction syndrome